The potential role of heparin-binding protein in neonatal sepsis: research progress - Chen, Xiyang; Li, Haiting; Li, Jie; Liu, Xixi; Chen, Linlin; Chen, Caie; Yuan, Junhui; Tao, Enfu (Frontiers in Cellular and Infection Microbiology, 2024)
Neonatal sepsis is a major global health challenge, leading to significant morbidity and mortality in newborns. The search for precise biomarkers for its early prediction in clinical settings has been ongoing, with heparin-binding protein (HBP) emerging as a promising candidate. Originating from granules in neutrophils, HBP is released into the bloodstream in response to infection and plays a pivotal role in the body’s inflammatory response. Its significance extends beyond its inflammatory origins; research indicates dynamic changes in HBP levels are strongly linked to reduce in-hospital mortality, offering a prognostic advantage over existing biomarkers. Furthermore, HBP has demonstrated considerable clinical utility in the early diagnosis and stratification of neonatal sepsis, suggesting its potential as a reliable blood marker for early prediction of the disease and its severity. Its application may extend to guiding the judicious use of antibiotics in treating newborns, addressing a critical aspect of neonatal care. Despite these encouraging results, the precise clinical utility of HBP for diagnosing and treating sepsis in neonates still demands further clarification through extensive research. This review delves into the current scientific understanding of HBP’s contribution to diagnosing, prognosticating, and treating neonatal sepsis, while considering its future clinical applications.